2019
DOI: 10.1177/1363461519858798
|View full text |Cite
|
Sign up to set email alerts
|

Idioms of resilience among cancer patients in urban South Africa: An anthropological heuristic for the study of culture and resilience

Abstract: Despite the large body of research on idioms of distress in anthropology and transcultural psychiatry, few scholars have examined the concepts that people use to describe social and psychological resilience. The experience of social and psychological resilience is embedded in and shaped by social, political, and economic contexts—much like the factors that shape idioms of distress. As resilience literature more broadly has adopted a socio-ecological rather than trait-based approach, anthropology has much to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 61 publications
(64 reference statements)
0
37
0
Order By: Relevance
“…Many patients describe acceptance of their diagnosis through their religious beliefs to be fundamental to their breast cancer experiences. 27 Churches are significant communities of care not only through fostering strength people find through religion but also through a community of dialogue around cancer detection, diagnosis, and treatment. Fostering discussion of what types of treatment exist to religious communities may stymie fear after diagnosis; also promoting dynamic supportive groups for people living through treatment is possible through religious spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients describe acceptance of their diagnosis through their religious beliefs to be fundamental to their breast cancer experiences. 27 Churches are significant communities of care not only through fostering strength people find through religion but also through a community of dialogue around cancer detection, diagnosis, and treatment. Fostering discussion of what types of treatment exist to religious communities may stymie fear after diagnosis; also promoting dynamic supportive groups for people living through treatment is possible through religious spaces.…”
Section: Discussionmentioning
confidence: 99%
“…But the women who struggled the most were those whose social worlds had eroded along with their illnesses, such as Ntabiseng. We found that a culturally defined notion of resilience-in this case, acceptance of one's conditions-may function as a critical mediator of interpersonal suffering between an individual and their family, as was the case for Mpumi (also see Kim et al, 2019).…”
Section: Resultsmentioning
confidence: 69%
“…Finally, Mpumi was living with breast cancer and hypertension and revealed how her cancer had an enormous social impact on her family, in this case a misfortune to her daughter's life, although she eventually learned to accept her physical conditions. These cases convey key themes that emerged across the 50 interviews and highlight the range of comorbid suffering that arose (also see other related publications; Kim et al, 2019;Mendenhall et al, 2019).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations